1999
DOI: 10.1159/000018262
|View full text |Cite
|
Sign up to set email alerts
|

Mutilating Facial Sarcoidosis

Abstract: We report a patient with massive facial sarcoidosis. While skin involvement is a common manifestation of sarcoidosis, it is unusual to see it in the dramatic form of cutaneous tumors with mutilation of the central face. There are few reports of tumoral cutaneous sarcoidosis like that of our patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Mutilating sarcoidosis appears to be a severe form of lupus pernio, with large centrofacial tumors and extension into the oral and upper respiratory tissue that resemble Wegener granulomatosis and malignant pleomorphic lymphoma. 61 One prospective study of 54 South Africans with skin sarcoidosis found that one quarter of patients presented with hypopigmented (Fig 4), ichthyosiform, lymphedematous, mutilating, ulcerative, verrucous, and other atypical forms. 62 Psoriasiform (Fig 5), lichenoid (Fig 6), verrucous (Fig 7), and angiolupoid (Fig 8) are variants of papular or plaque sarcoidosis that can be confused with psoriasis, lichen planus, warts (or lichen simplex chronicus), or lupus erythematosus, respectively.…”
Section: Cutaneous Disease Key Pointsmentioning
confidence: 99%
“…Mutilating sarcoidosis appears to be a severe form of lupus pernio, with large centrofacial tumors and extension into the oral and upper respiratory tissue that resemble Wegener granulomatosis and malignant pleomorphic lymphoma. 61 One prospective study of 54 South Africans with skin sarcoidosis found that one quarter of patients presented with hypopigmented (Fig 4), ichthyosiform, lymphedematous, mutilating, ulcerative, verrucous, and other atypical forms. 62 Psoriasiform (Fig 5), lichenoid (Fig 6), verrucous (Fig 7), and angiolupoid (Fig 8) are variants of papular or plaque sarcoidosis that can be confused with psoriasis, lichen planus, warts (or lichen simplex chronicus), or lupus erythematosus, respectively.…”
Section: Cutaneous Disease Key Pointsmentioning
confidence: 99%
“…45,46 The most frequent clinical manifestation of the great imitator is its papular or nodular form (Fig. 53 Ulcerative sarcoidosis shows a predilection for young adults and most often affects women and individuals of African or Japanese descent. The patient's face rarely remains unaffected.…”
Section: Cutaneous Manifestationsmentioning
confidence: 99%
“…Its differential diagnosis includes leprosy, granulomatous rosacea, Wegener's granulomatosis, and malignant pleomorphic lymphoma. 53 Ulcerative sarcoidosis shows a predilection for young adults and most often affects women and individuals of African or Japanese descent. Ulcers tend to arise within existing papulonodules on the lower legs but may occur on previously normal skin with a generalized distribution.…”
Section: Cutaneous Manifestationsmentioning
confidence: 99%
“…Lupus pernio is characterized by violaceous or erythematous indured papules, plaques, or nodules that are primarily distributed on the central face [138]. The alar rim of the nose is often affected.…”
Section: E Lupus Perniomentioning
confidence: 99%
“…The alar rim of the nose is often affected. Lupus pernio is more common in women than in men and is associated with chronic disease and extrapulmonary involvement [138,139]. Without treatment, the lesions progressively increase in thickness, size, and induration, eventually resulting in considerable cosmetic disfigurement.…”
Section: E Lupus Perniomentioning
confidence: 99%